A robot off-line programming system for welding intersecting pipe. (September 2019) - Yang, Li; Hong, Lei; Ji, Baojian
Abstract: In order to meet the requirements of welding intersecting line welds, an off-line programming system is designed. The off-line programming system is developed with SolidWorks API functions, includes kinematics analysis, trajectory planning, off-line simulation and other modules. The system is applied to an ABB welding robot with six revolute joints. The welding experiment of the robot cylindrical intersecting pipe is carried out, and the experimental results verify the system.